Physicochemical and electrochemical performance of LiFe1−xNixPO4 (0≤x≤1.0) solid solution as potential cathode material for rechargeable lithium-ion battery. Issue 7 (May 2017) - Saroha, Rakesh; Panwar, Amrish K.; Sharma, Yogesh
Abstract: In this work, olivine-type LiFePO4 (LFP) and nickel (Ni) substituted LiFe1- x Ni x PO4 (0≤ x ≤1.0) solid solutions were synthesized using the wet-milling route. Synthesized samples were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). XRD results show that all the samples were crystallized in the orthorhombic phase with Pnma space group and no secondary phase was detected even at higher Ni-concentration. Rietveld refinement results reveal that average distance increases up to x =0.03 (LFNP3) and decrease thereafter monotonically on further increase in Ni-concentration. Moreover, the LFNP3 sample shows highest electrical conductivity as compared to other solid solutions. Among the synthesized samples for x ≤0.1, LFNP3 shows highest discharge capacity at all C-rates. LFNP3 exhibits a discharge capacity of 158 (±5) mAh g −1 at 0.1 C (almost 93% of the theoretical capacity) and displays the high and stable discharge capacity of 145 (±5) mAh g −1 at 1 C rate for 150 charge/discharge cycles. Among high Ni content (0.1< x ≤1.0) samples, LiFe0.7 Ni0.3 PO4 (LFNP30) delivers best charge/discharge capacity at all C-rates. LFNP30 exhibits a discharge capacity of 90 (±5) mAh g −1 at 0.1 C rate.